Anthrax outbreak in Nigeria: Government initiatives and response to protect livestock and public health - Jafar Usman; Fatima Sanusi; Ahmad Balarabe; Ubaida Muhammad (Microbes and Infectious Diseases)
On July 17, 2023, the Federal Ministry of Agriculture and Rural Development (FMARD) formally recognized a single instance of anthrax disease on a farm with a variety of animals in Niger State. Since the West African outbreak started in Ghana in June 2023, this is the first instance of the disease in an animal that has been documented in Nigeria. There were eight casualties as a result of the unplanned death of cattle on this farm, according to a report published on July 13th, 2023. Additionally, bleeding from outside openings in these dead animals was seen, and this bleeding did not require typical blood coagulation. Another incident of anthrax disease was documented on July 30, 2023, in Lagos, the most densely populated state in Nigeria. Six animals within the state have been definitively identified as having contracted the illness. These occurrences were detected while conducting routine monitoring of animals on both Lagos Island and Agege. As a precautionary measure against the further propagation of the ailment, the concern agency has since confiscated, incinerated, and interred the afflicted animals. Several weeks prior to the epidemic, the Federal Ministry of Agriculture and Rural Development (FMARD) issued a warning to the general populace about the emergence of Anthrax in certain neighboring nations of Nigeria located in the West African Sub-Region. In particular, this outbreak was identified along the northern border of Ghana, adjacent to Burkina Faso Togo.